Decision support system for optimum decision making process in threat evaluation and weapon assignment: Current status, challenges and future directions. (2017) - Naseem, Afshan; Shah, Syed Tasweer Hussain; Khan, Shoab Ahmed; Malik, Asad Waqar
Abstract: While advancement trends in 'Decision Support System' have frequently been reported in air defense literature, a gap still exists to present a holistic viewpoint for management of threat evaluation and weapon assignment (TEWA). This study reviewed 156 papers from peer reviewed journals and conference proceedings published during 1975 to 2016. The current status of TEWA indicates several challenges associated with decision support system, most notably, application of technological advancement for the better human control in critical time constraint situations. For better decision making and overcoming human limitations, the technological advancements in decision support system are promising. This paper proposes a new approach and presents a combination of decision support system and threat perception, with simultaneous evaluation, neutralization, weapon supply, inventory and assignment. In this study, we have reviewed the evolution in development of threat neutralization systems which have been attempted or developed to date. From practical perspective, the study provides a design overview of the existing methods, highlights features/merits of the approaches used in decision support system development. We have also discussed the current challenges regarding such applications and proposed a new approach for efficient and effective TEWA. The proposed approach elucidates the significance of the inclusion of new parameters identified in literature review. Some of the important features of proposed TEWA-DSS are: (1) GIS mapping of vulnerable assets/points (VA/VPs), (2) Weapon Deployment (WD) based on criticality of VA/VPs and using forecasting techniques, (3) Threat Perception (TP), and evaluation, (4) operating tactics, (5) Weapons Selection (WS) based on its supply chain and inventory management using forecasting methods and (6) optimum and cost-effective Weapon Assignment (WA). The SWOT analysis of the proposed model shows the significance of this model. Moreover, the model implementation using Simon and Turban phases of decision making processes showed that the proposed TEWA strategy is an effective and efficient tool for the identified problem of optimum decision making. This study will catch the attention of researchers working on DSS and open new horizons to bring remarkable improvement in existing system by incorporating the missing parameters.